Design and Evaluation of Smartphone-based 3D Interaction for Large Display - Lee, Dongwoo; Hwang, Jae-In (2015 IEEE INTERNATIONAL CONFERENCE ON CONSUMER ELECTRONICS (ICCE), 2015)
In this paper, we present a novel 3D interaction technique using a smartphone for large screen such as TV and projector screen. Using our 3D interaction technique, we could manipulate 3D objects in 3D environment with the virtual hand metaphor. Also, we evaluate the effects of various sensory inputs such as vibro-tactile, auditory and visual inputs. The result of the user study shows that visual feedback is not significantly different from combinations of other sensory feedbacks. Our 3D interaction method and the evaluation result can be applied to various areas including shopping and game.